Genetic diversity assessment and estimation of phylogenetic relationships among 26 Fagaceae species using ISSRs - Coutinho, João Paulo; Carvalho, Ana; Lima-Brito, José (Biochemical Systematics and Ecology, 2014)
The family Fagaceae includes several species and presents huge genetic variability. In the last two decades, several genetic studies about phylogenetics and genetic diversity of Fagaceae have emerged. ISSR markers were used to evaluate the genetic diversity of 26 species of Fagaceae belonging to the genera Castanea, Fagus and Quercus. Among several primers tested, 17 were selected for the evaluation of diversity and estimation of genetic relationships. A total of 371 ISSR markers were produced and each primer revealed high polymorphism. Specific ISSR markers for the Quercus infrageneric groups were amplified. ISSRs proved to be a reliable tool for the discrimination of the analyzed species per genus, infrageneric group and/or ecological origin.
Keywords: Fagaceae; Genetic variability; Inter-simple sequence repeats (ISSRs); Quercus

Molecular Organization of the 25S-18S rDNA IGS of Fagus sylvatica and Quercus suber: A Comparative Analysis. - Inácio, Vera; Rocheta, Margarida; Morais-Cecílio, Leonor (PloS one, 2014)
The 35S ribosomal DNA (rDNA) units, repeated in tandem at one or more chromosomal loci, are separated by an intergenic spacer (IGS) containing functional elements involved in the regulation of transcription of downstream rRNA genes. In the present work, we have compared the IGS molecular organizations in two divergent species of Fagaceae, Fagus sylvatica and Quercus suber, aiming to comprehend the evolution of the IGS sequences within the family. Self- and cross-hybridization FISH was done on representative species of the Fagaceae. The IGS length variability and the methylation level of 18 and 25S rRNA genes were assessed in representatives of three genera of this family: Fagus, Quercus and Castanea. The intergenic spacers in Beech and Cork Oak showed similar overall organizations comprising putative functional elements needed for rRNA gene activity and containing a non-transcribed spacer (NTS), a promoter region, and a 5'-external transcribed spacer. In the NTS: the sub-repeats structure in Beech is more organized than in Cork Oak, sharing some short motifs which results in the lowest sequence similarity of the entire IGS; the AT-rich region differed in both spacers by a GC-rich block inserted in Cork Oak. The 5'-ETS is the region with the higher similarity, having nonetheless different lengths. FISH with the NTS-5'-ETS revealed fainter signals in cross-hybridization in agreement with the divergence between genera. The diversity of IGS lengths revealed variants from ∼2 kb in Fagus, and Quercus up to 5.3 kb in Castanea, and a lack of correlation between the number of variants and the number of rDNA loci in several species. Methylation of 25S Bam HI site was confirmed in all species and detected for the first time in the 18S of Q. suber and Q. faginea. These results provide important clues for the evolutionary trends of the rDNA 25S-18S IGS in the Fagaceae family.
APS
Keywords: chromosomal loci; Fagaceae; Fagus sylvatica; intergenic spacer; Quercus suber; ribosomal DNA

Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Genomic organization and dynamics of repetitive DNA sequences in representatives of three Fagaceae genera - Alves, Sofia; Ribeiro, Teresa; Inácio, Vera; Rocheta, Margarida; Morais-Cecílio, Leonor (Genome, 2012)
Oaks, chestnuts, and beeches are economically important species of the Fagaceae. To understand the relationship between these members of this family, a deep knowledge of their genome composition and organization is needed. In this work, we have isolated and characterized several AFLP fragments obtained from Quercus rotundifolia Lam. through homology searches in available databases. Genomic polymorphisms involving some of these sequences were evaluated in two species of Quercus, one of Castanea, and one of Fagus with specific primers. Comparative FISH analysis with generated sequences was performed in interphase nuclei of the four species, and the co-immunolocalization of 5-methylcytosine was also studied. Some of the sequences isolated proved to be genus-specific, while others were present in all the genera. Retroelements, either gypsy-like of the Tat/Athila clade or copia-like, are well represented, and most are dispersed in euchromatic regions of these species with no DNA methylation associated, pointing to an interspersed arrangement of these retroelements with potential gene-rich regions. A particular gypsy-sequence is dispersed in oaks and chestnut nuclei, but its confinement to chromocenters in beech evidences genome restructuring events during evolution of Fagaceae. Several sequences generated in this study proved to be good tools to comparatively study Fagaceae genome organization.
doi: 10.1139/g2012-020doi: 10.1139/g2012-020The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: AFLP; Castanea; euchromatin; Fagaceae; Fagus; Quercus; retroelements

Improved Genetic Transformation of Cork Oak (Quercus suber L.) - Álvarez-Fernández, Rubén; Ordás, Ricardo-Javier (Plant Cell Culture Protocols SE - 28, 2012)
An Agrobacterium-mediated transformation system for selected mature Quercus suber L. trees has been established. Leaf-derived somatic embryos in an early stage of development are inoculated with an AGL1 strain harboring a kanamycin-selectable plasmid carrying the gene of interest. The transformed embryos are induced to germinate and the plantlets transferred to soil. This protocol, from adult cork oak to transformed plantlet, can be completed in about one and a half years. Transformation efficiencies (i.e., percentage of inoculated explants that yield independent transgenic embryogenic lines) vary depending on the cork oak genotype, reaching up to 43%.
The following values have no corresponding Zotero field: periodical: Plant Cell Culture Protocols SE - 28 electronic-resource-num: 10.1007/978-1-61779-818-4_28
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; Herbicide Resistance; kanamycin resistance; Quercus suber; Somatic embryogenesis; Tree genetic transformation

Cryphonectria naterciae: a new species in the Cryphonectria-Endothia complex and diagnostic molecular markers based on microsatellite-primed PCR. - Bragança, Helena; Rigling, Daniel; Diogo, Eugénio; Capelo, Jorge; Phillips, Alan; Tenreiro, Rogério (Fungal biology, 2011)
In a recent study intended to assess the distribution of Cryphonectria parasitica in Portugal, 22 morphologically atypical orange isolates were collected in the Midwestern regions. Eleven isolates were recovered from Castanea sativa, in areas severely affected by chestnut blight and eleven isolates from Quercus suber in areas with cork oak decline. These isolates were compared with known C. parasitica and Cryphonectria radicalis isolates using an integrated approach comprising morphological and molecular methods. Morphologically the atypical isolates were more similar to C. radicalis than to C. parasitica. Phylogenetic analyses based on internal transcribed spacer (ITS) and β-tubulin sequence data grouped the isolates in a well-supported clade separate from C. radicalis. Combining morphological, cultural, and molecular data Cryphonectria naterciae is newly described in the Cryphonectria-Endothia complex. Microsatellite-primed PCR fingerprinting with (GACA)(4) primer discriminated between C. naterciae, C. radicalis, and C. parasitica.
The following values have no corresponding Zotero field: accession-num: 21872182
Keywords: Ascomycota; Ascomycota: classification; Ascomycota: genetics; Ascomycota: isolation & purification; Chestnut tree; Cork oak tree; Cryphonectria parasitica; Cryphonectria radicalis (GACA)4; DNA; DNA Primers; DNA Primers: genetics; Endothiella gyrosa; Fagaceae; Fagaceae: microbiology; Fungal; Fungal Proteins; Fungal Proteins: genetics; Fungal: genetics; Microsatellite Repeats; Molecular Sequence Data; MSP-PCR; Mycological Typing Techniques; Mycological Typing Techniques: methods; phylogeny; Plant Diseases; Plant Diseases: microbiology; Polymerase Chain Reaction; Polymerase Chain Reaction: methods; Quercus; Quercus: microbiology; RFLP-PCR; Tubulin; Tubulin: genetics

Erinea formation on Quercus ilex leaves: anatomical, physiological and chemical responses of leaf trichomes against mite attack. - Karioti, Anastasia; Tooulakou, Georgia; Bilia, Anna Rita; Psaras, George K.; Karabourniotis, George; Skaltsa, Helen (Phytochemistry, 2011)
Structures on the surfaces of leaves, such as dense layers of non-glandular trichomes, strongly affect phylloplane mite activities. On the other hand the feeding of eriophyoid mites on leaf surfaces can cause hyperplasia of leaf trichomes (erinea formation). In many cases the hyperplasia is accompanied by the accumulation of pigments within trichome cells, causing an impressive red-brown colouration of the erineum. There is no information, however, on the structure of these pigments as well as on the chemical alterations in the phenolic content of plant trichomes in response to mite attack. Erinea formation on the abaxial surface of Quercus ilex leaves upon Aceria ilicis (Acari: Eriophyoidea) attack provides an excellent model on this topic. Differences in the structure and chemical composition of isolated trichomes derived either from healthy (normal trichomes) or mite attacked (hypertrophic trichomes) leaves were examined. Carbon investment was comparable between the two different trichome types, but the cell walls of the hypertrophic trichomes appeared thinner and did not contain microcrystalline cellulose. Observations under the fluorescence microscope showed that the emitted fluorescence was different between the two trichome types, indicating a different composition in fluorescencing phenolic compounds. The chemical analyses confirmed that hypertrophic trichomes contained higher concentrations of the feeding deterrents proanthocyanidin B3 and catechin, as well as of quercetin-3-O-glucoside, but lower concentrations of acylated flavonoid glycosides, than the normal ones. The results showed that the structural and functional changes in leaf trichomes upon mite attack may be an effort of the leaf to compensate the damage caused by the pest.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21131012
Keywords: Fagaceae; Leaf trichomes; Mites; phenolics; Quercus ilex

Predicting understory maximum shrubs cover using altitude and overstory basal area in different Mediterranean forests - Coll, Lluís; González-Olabarria, José Ramón; Mola-Yudego, Blas; Pukkala, Timo; Messier, Christian (European Journal of Forest Research, 2010)
In some areas of the Mediterranean basin where the understory stratum represents a critical ﬁre hazard, managing the canopy cover to control the understory shrubby vegetation is an ecological alternative to the current mechanical management techniques. In this study, we determine the relationship between the overstory basal area and the cover of the understory shrubby vegetation for different dominant canopy species (Pinaceae and Fagaceae species) along a wide altitudinal gradient in the province of Catalonia (Spain). Analyses were conducted using data from the Spanish National Forest Inventory. At the regional scale, when all stands are analysed together, a strong negative relationship between mean shrub cover and site elevation was found. Among the Pinaceae species, we found fairly good relationships between stand basal area and the maximum development of the shrub stratum for species located at intermediate elevations (Pinus nigra, Pinus sylvestris). However, at the extremes of the elevationclimatic gradient (Pinus halepensis and Pinus uncinata stands), stand basal area explained very little of the shrub cover variation probably because microsite and topographic factors override its effect. Among the Fagaceae species, a negative relationship between basal area and the maximum development of the shrub stratum was found in Quercus humilis and Fagus sylvatica dominated stands but not in Quercus ilex. This can be due to the particular canopy structure and management history of Q. ilex stands. In conclusion, our study revealed a marked effect of the tree layer composition and the environment on the relationship between the development of the understory and overstory tree structure. More ﬁne-grained studies are needed to provide forest managers with more detailed information about the relationship between these two forest strata.
Keywords: á altitude á; á fagaceae; Altitude; Basal area; e47; european network for forest; Fagaceae; Overstory; overstory á basal area; Pinaceae; Shrub cover; shrub cover á pinaceae; the cost action; the final conference of; this article originates from; vegetation management

Proanthocyanidin glycosides from the leaves of Quercus ilex L. (Fagaceae) - Karioti, Anastasia; Bilia, Anna Rita; Gabbiani, Chiara; Messori, Luigi; Skaltsa, Helen (Tetrahedron Letters, 2009)
From the polar extracts of the leaves of Quercus ilex L., two new proanthocyanidin glycosides, namely afzelechin-(4a?8)-catechin-3-O-b-glucopyranoside (1) and afzelechin-(4a?8)-catechin-3-O-a-rhamnopyranoside (2), were isolated in addition to catechin (3), proanthocyanidin B3 (4), prodelphinidin C (5), dehydrodicatechin A (6), quercetin (7) and six known ﬂavonol glucosides with their acylated derivatives (8–13) and ellagic acid (14). The structures of all isolated compounds were established by spectroscopic means, mainly 1D and 2D NMR, as well as LC/MS and HR-MS spectrometric analyses. The absolute con- ﬁguration of compound 1 was determined by CD measurements. The proanthocyanidin glycosides are especially interesting, as they possess the sugar in the upper unit of the dimer, which is rare for this type of compounds.
Keywords: Circular dichroism; Fagaceae; Oak-leaves; Proanthocyanidin glycosides; Quercus ilex; ROESY

Crystal macropatterns in leaves of Fagaceae and Nothofagaceae: a comparative study - Lersten, N. R.; Horner, Harry T. (Plant Systematics and Evolution, 2008)
Crystal macropatterns in Fagaceae and Nothofagaceae were examined from cleared herbarium leaves (eight genera, 122 spp.) by polarizing microscopy. Prisms and druses dominate, but previously undescribed intermediate forms occur in 25 species of Fagaceae. Sixty-two species had only prisms associated with vein orders 1–4, but smallest orders 5 and 6 had few or no crystals. In mesophyll, 98 species had small druses in spongy parenchyma and larger but fewer druses in palisade parenchyma. Subfamily Fagoideae conformed closely to this macropattern, Castaneoideae less so. Six Castaneoideae species lacked vein crystals. Two Fagoideae species and seven Nothofagus species lacked mesophyll crystals. Druses with prominent cores occur throughout Fagaceae but none were seen in Nothofagaceae. Tabular presentation of results shows signiﬁcant although overlapping trends from Fagoideae to Castaneoideae to Nothofagaceae, with the latter taxon deviating most from Fagaceae.
Keywords: Calcium oxalate; crystals; Fagaceae; leaf anatomy; macropatterns; Nothofagaceae

Phenolic variations in mite infected leaves of Quercus ilex L. (Fagaceae) - Karioti, A; Tooulakou, G; Karabourniotis, G; Bilia, A R; Skaltsa, H (PLANTA MEDICA, 2008)
Structures on the surfaces of leaves, such as dense layers of non-glandular trichomes, strongly affect phylloplane mite activities. On the other hand the feeding of eriophyoid mites on leaf surfaces can cause hyperplasia of leaf trichomes (erinea formation). In many cases the hyperplasia is accompanied by the accumulation of pigments within trichome cells, causing an impressive red-brown colouration of the eri- neum. There is no information, however, on the structure of these pigments as well as on the chemical alterations in the phenolic content of plant trichomes in response to mite attack. Erinea formation on the abaxial surface of Quercus ilex leaves upon Aceria ilicis (Acari: Eriophyoidea) attack provides an excel- lent model on this topic. Differences in the structure and chemical composition of isolated trichomes derived either from healthy (normal trichomes) or mite attacked (hypertrophic trichomes) leaves were examined. Carbon investment was comparable between the two different trichome types, but the cell walls of the hypertrophic trichomes appeared thinner and did not contain microcrystalline cellulose. Observations under the fluorescence microscope showed that the emitted fluorescence was different between the two trichome types, indicating a different composition in fluorescencing phenolic com- pounds. The chemical analyses confirmed that hypertrophic trichomes contained higher concentrations of the feeding deterrents proanthocyanidin B3 and catechin, as well as of quercetin-3-O-glucoside, but lower concentrations of acylated flavonoid glycosides, than the normal ones. The results showed that the structural and functional changes in leaf trichomes upon mite attack may be an effort of the leaf to compensate the damage caused by the pest
Keywords: Fagaceae; Leaf trichomes; Mites; phenolics; Quercus ilex

A novel dimeric proanthocyanidin 3-O-glucoside from Quercus ilex L. (Fagaceae) - Karioti, A.; Bilia, A. R.; Skaltsa, H. (PLANTA MEDICA, 2007)
ity at room temperature in order to deactivate any enzymes and avoid polymerizations and oxidations. Final extraction was carried out using MeOH and MeOH/H2O 8/2. A fast fractionation of the residue was done using VLC over silica gel followed by repeated cc over Sephadex LH-60 and Sephadex LH-20. Fractionations were monitored with HPLC-DAD-MS. The structures of the isolated compounds were established by means of 1D & 2D NMR.
Keywords: Circular dichroism; Fagaceae; Oak-leaves; Proanthocyanidin glycosides; Quercus ilex; ROESY

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Quero, José Luis; Villar, Rafael; Marañón, Teodoro; Zamora, Regino; Poorter, Lourens (American Journal of Botany 94(11):, 2007)
Three hypotheses have been proposed to explain the functional relationship between seed mass and seedling performance: the reserve effect (larger seeds retain a larger proportion of reserves after germinating), the metabolic effect (seedlings from larger seeds have slower relative growth rates), and the seedling-size effect (larger seeds produce larger seedlings). We tested these hypotheses by growing four Mediterranean Quercus species under different light conditions (3, 27, and 100% of available radiation). We found evidence for two of the three hypotheses, but none of the four species complied with all three hypotheses at the same time. The reserve effect was not found in any species, the metabolic effect was found in three species (Q. ilex, Q. pyrenaica, and Q. suber), and the seedling-size effect in all species. Light availability significantly affected the relationships between seed size and seedling traits. For Q. ilex and Q. canariensis, a seedling-size effect was found under all three light conditions, but only under the lowest light (3%) for Q. suber and Q. pyrenaica. In all species, the correlation between seed mass and seedling mass increased with a decrease in light, suggesting that seedlings growing in low light depend more upon their seed reserves. A causal model integrates the three hypotheses, suggesting that larger seeds generally produced larger seedlings.
From Duplicate 2 ( SEED - MASS EFFECTS IN FOUR MEDITERRANEAN QUERCUS SPECIES (FAGACEAE ) GROWING IN CONTRASTING LIGHT ENVIRONMENTS - Environments, Contrasting Light; Uero, L U I S Q; Illar, R Afael V; Aran, T Eodoro M; Oorter, L Ourens P; Ciencias, Facultad De; Granada, Universidad De; Ecologı, A De )
Keywords: acornmass; Fagaceae; light availability; mediterranean oaks; Quercus; RGR; Seed size; seed–seedling relationships

Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: periodical: Methods in molecular biology (Clifton, N.J.) accession-num: 17033056 electronic-resource-num: 10.1385/1-59745-131-2:113
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase

Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Álvarez, R; Alonso, P; Cortizo, M; CELESTINO, C; HERNÁNDEZ, I; TORIBIO, M; Ordás, R J (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation

Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Alvarez, R.; Alonso, P.; Cortizo, M.; Celestino, C.; Hernández, I.; Toribio, M.; Ordás, R. J. (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: accession-num: 15185122
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation

Testing the conservation of Quercus spp. microsatellites in the cork oak, Q-suber L. - Hornero, J; Gallego, F J; Martinez, I; TORIBIO, M (SILVAE GENETICA, 2001)
The transferability of microsatellite (SSR) loci from Quercus spp. to cork oak (Quercus suber L.) was investigated. Semi-automated analysis of fluorescently-labelled PCR fragments was used to test 24 primer sets developed for Q. myrsinifolia BLUME, Q. petraea (MAT7.) LIEB. and Q. robur L. in 41 cork oak trees from four stands covering the main area of distribution of the species in Spain. Successful cross-species events occurred for 13 loci (54%). Two of them were monomorphic and another two appeared as multilocus. High levels of genetic variability were detected both for the number of alleles, 62 (7.5 per polymorphic locus, with a maximum number of 19 in locus ssrQpZAG110) and for the expected heterozygosity (mean H-E = 0.648). These results were much higher than those previously reported by other authors using allozyme loci. The usefulness of the. SSR loci successfully amplified for studies on population genetics of cork oak is discussed.
Keywords: Cork oak; Fagaceae; microsatellites; Quercus suber

Apoplastic Solute Concentrations of Organic Acids and Mineral Nutrients in the Leaves of Several Fagaceae - Gabriel, Reinhard; Kesselmeier, Jürgen (Plant and Cell Physiology, 1999)
Ion chromatographic methods determined organic acids and main nutrient minerals in the apoplastic solution from leaves of several Fagaceae (Quercus ilex L., Quercus cerris L., Quercus virgiliana (Ten.) Ten, and Fagus sylvatica L.). The anions of organic acids found in high amounts (250 to 650 μM) were quinate, malate, and oxalate. Lactate, pyruvate, formate and acetate were detected in relatively low amounts with concentrations between 20 and 200 μM. The total concentration of organic acids in the apoplastic sap ranged between 1.5 and 2 mM. The total concentration of inorganic cations (K+, Mg2+, NH4+, Ca2+, Na+) and anions (C1−, NO3−, SO2−4 and PO3−4) in the apoplastic sap varied between 5 and 10 mM, and 0.35 and 1.8 mM, respectively. We conclude that the concentration of organic acid ions in the leaf apoplast depends mainly on the exchange with the leaf cells and is influenced by the electrochemical gradient between the symplast and the apoplast in relation to the water potential of the leaf. The determination of formate and acetate in the apoplastic compartment of leaves lend weight to the argument that the production of these acids by trees is a important emission source to the atmosphere.
Keywords: Anions; Apoplast; cations; Fagaceae; leaf; organic acids

Apoplastic Solute Concentrations of Organic Acids and Mineral Nutrients in the Leaves of Several Fagaceae - Gabriel, Reinhard; Kesselmeier, Jürgen (Plant and Cell Physiology, 1999)
Ion chromatographic methods determined organic acids and main nutrient minerals in the apoplastic solution from leaves of several Fagaceae (Quercus ilex L., Quercus cerris L., Quercus virgiliana (Ten.) Ten, and Fagus sylvatica L.). The anions of organic acids found in high amounts (250 to 650 μM) were quinate, malate, and oxalate. Lactate, pyruvate, formate and acetate were detected in relatively low amounts with concentrations between 20 and 200 μM. The total concentration of organic acids in the apoplastic sap ranged between 1.5 and 2 mM. The total concentration of inorganic cations (K+, Mg2+, NH4+, Ca2+, Na+) and anions (C1−, NO3−, SO2−4 and PO3−4) in the apoplastic sap varied between 5 and 10 mM, and 0.35 and 1.8 mM, respectively. We conclude that the concentration of organic acid ions in the leaf apoplast depends mainly on the exchange with the leaf cells and is influenced by the electrochemical gradient between the symplast and the apoplast in relation to the water potential of the leaf. The determination of formate and acetate in the apoplastic compartment of leaves lend weight to the argument that the production of these acids by trees is a important emission source to the atmosphere.
Keywords: Anions; Apoplast; cations; Fagaceae; leaf; organic acids

ITS sequences from nuclear rDNA suggest unexpected phylogenetic relationships between Euro-Mediterranean, East Asiatic and North American taxa ofQuercus ( - Samuel, Rosabelle; Bachmair, Andreas (Plant systematics and …, 1998)
Nucleotide sequences from the internal transcribed spacer (ITS) regions of the 18S-26S nuclear ribosomal DNA have been studied from ten species of Quercus (representing four subgenera), Castanea sativa and Fagus sylvatica, as a preliminary molecular contribution to the still poorly understood systematics and evolution of Fagaceae. The resulting matrix has been used to calculate pair-wise sequence divergence indices and to construct a maximum parsimony tree for Quercus coding indels as a fifth state. Divergence is greater for Quercus vs. Fagus than for Quercus vs. Castanea. The tree for the Quercus taxa studied reveals two clearly divergent clades. In clade I the evergreen W Mediterranean Q. suber appears in a basal position as sister to more distal deciduous taxa, i.e. the E Mediterranean Q. macrolepis and the E Asiatic Q. acutissima (all formerly united as different sections under the apparently polyphyletic subg. Cerris), and Q. rubra (a representative of the N American subg. Erythrobalanus), forming a pair with Q. acutissima. In clade II the evergreen southeastem N American Q. virginiana is basal and sister to the remaining three branches, i.e. a pair of evergreen Mediterranean taxa with Q. ilex and Q. coccifera (subg. Sclerophyllodrys), the deciduous but otherwise plesiomorphic SE European/SW Asiatic Q. cerris (type species of subg. Cerris), and the related but more apomorphic European pair Q. petraea and Q. robur (subg. Quercus). These results partly conflict with current taxonomic classification but a_re supported by some anatomical and morphological characters. They document polyphyletic lines from evergreen to deciduous taxa and suggest Tertiary transcontinental connections within the genus.
Keywords: Castanea; Fagaceae; Fagus. - Nuclear rDNA; ITS; molecular phylogeny; molecular systematics; N Hemisphere; Phytogeography; Quercus

Anatomical changes and evolutionary trends in the foliar epidermis of extant and fossil Euro-Mediterranean oaks (Fagaceae) - Uzunova, K; Palamarev, E; Ehrendorfer, F (Plant systematics and Evolution, 1997)
The differentiation of foliar epidermis structures, cuticles, stomata, and indumen- turn of most of the extant Euro-Mediterranean taxa of Quercus have been studied by light and scanning electron microscopy, and compared with other genera and fossil material. Results allow the recognition of the subgg. Sclerophyllodrys, Cerris and Quercus, and of various sections and even individual species. The cyclocytic stomata type, regarded as plesiomorphic, is found in the geologically oldest representatives of the familiy (DryophylIum, resp. Eotrigonobalanus) and in the relatively old, evergreen to semi-evergreen species of Quercus subgg. Sclerophyllodrys and Cerris. These taxa also have relatively thick and smooth cuticles. Anomocytic stomata, thinner cuticles and the presence of crystalline wax flakes are regarded as apomorphic features and characterize the deciduous taxa ofsubg. Quercus. These changes are interpreted as ecological adaptations to the changing climates from the Tertiary to the present. An analysis of the various character combinations found in macrofossils and the often poor species separation i n Quercus suggest that hybridization has played a major role in the evolution of the Euro-Mediterranean oaks.
Keywords: epidermis characters; evolutionary trends; Fagaceae; fossil and extant taxa; Quercus

Anatomical changes and evolutionary trends in the foliar epidermis of extant and fossil Euro-Mediterranean oaks (Fagaceae) - Uzunova, K.; Palamarev, E.; Ehrendorfer, F. (Plant systematics and Evolution, 1997)
The differentiation of foliar epidermis structures, cuticles, stomata, and indumen- turn of most of the extant Euro-Mediterranean taxa of Quercus have been studied by light and scanning electron microscopy, and compared with other genera and fossil material. Results allow the recognition of the subgg. Sclerophyllodrys, Cerris and Quercus, and of various sections and even individual species. The cyclocytic stomata type, regarded as plesiomorphic, is found in the geologically oldest representatives of the familiy (DryophylIum, resp. Eotrigonobalanus) and in the relatively old, evergreen to semi-evergreen species of Quercus subgg. Sclerophyllodrys and Cerris. These taxa also have relatively thick and smooth cuticles. Anomocytic stomata, thinner cuticles and the presence of crystalline wax flakes are regarded as apomorphic features and characterize the deciduous taxa ofsubg. Quercus. These changes are interpreted as ecological adaptations to the changing climates from the Tertiary to the present. An analysis of the various character combinations found in macrofossils and the often poor species separation i n Quercus suggest that hybridization has played a major role in the evolution of the Euro-Mediterranean oaks.
Keywords: epidermis characters; evolutionary trends; Fagaceae; fossil and extant taxa; Quercus

UV-B protective potential and flavonoid content of leaf hairs of Quercus ilex - Skaltsa, Helen; Verykokidou, Evmorphia; Harvala, Catherine; Karabourniotis, George; Manetasi, Yiannis (Phytochemistry, 1994)
Flavonoids of non-glandular leaf hairs from Quercus ilex were analysed. The main compounds were acylated kaempferol glycosides. Acylation shifted the absorption peak into the ultraviolet-B region of the spectrum in which intact trichome layers absorbed strongly. Ultraviolet-B radiation caused a considerable reduction of photosystem II photochemical efficiency only in dehaired leaves. It is suggested that leaf hairs, besides other roles, may function as an effective filter against the harmful ultraviolet-B radiation.
Keywords: Fagaceae; flavonoids; Holly Oak; leaf hairs; Quercus ilex; UV-B damage

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - LO GULLO, M A; Salleo, S (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - Lo Gullo, M. A.; Salleo, S. (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R; Delre, V; Schirone, B; Maggini, F (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R.; Delre, V.; Schirone, B.; Maggini, F. (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy

Water balance of Eucalyptus globulus and Quercus suber forest stands in south Portugal - PEREIRA DE ALMEIDA, A; RIEKERK, H (Forest ecology and management, 1990)
The study utilized two watersheds near the town of Odemira in Alentejo, a southern province of Portugal. The region has a relatively humid climate because of its proximity to the sea. One 6-ha watershed contained scattered native cork oak (Quercus suber) with a newly developing understory of shrubs. An adjacent 19-ha watershed contained a mature Eucalyptus globulus stand, which was harvested for the study. The study included measurements of precipitation, runoff and soil water storage. Measurements of the tree stands and canopies were included for the characterization of throughfall and stemflow
Keywords: Angiospermae; Anthropogenic factor; Arbol forestal frondoso; Arbre forestier feuillu; Artificial forest stand; Balance agua; Bilan eau; Bosque; Dicotyledones; Eucalyptus globulus; Europa; EUROPE; Facteur anthropique; Factor antrópico; Fagaceae; Forests; forêt; Hardwood forest tree; Mediterranean vegetation; Myrtaceae; Peuplement forestier artificiel; Poblamiento forestal artificial; Portugal; Quercus suber; Spermatophyta; Vegetación mediterránea; Végétation méditerranéenne; Water balance (citation)

Free and bound hydroxyl and carboxyl groups in the cutin of Quercus suber leaves - Agulló, C; Collar, C; Seoane, E (Phytochemistry, 1984)
The number of free and bound hydroxyl and carboxyl groups of the cutin of Quercus suber leaves was investigated by the lithium borohydride hydrogenolysis of mesyl-cutin compared with the lithium borohydride hydrogenolysis of untreated cutin. Fifty per cent of the vic-diol groups of the trihydroxy C18 acid component and twenty five per cent of the secondary hydroxyl groups of the dihydroxy C16 acid component are free. The rest of the secondary and all of the primary hydroxyl groups are esterified; all carboxyl groups are esterified.
Keywords: cutin; Fagaceae; free hydroxyl groups; hydrogenolysis; leaves; mesyl-cutin; Quercus suber

Pollen grain morphology supports the taxonomical discrimination of Mediterranean oaks (Quercus, Fagaceae) - Colombo, P M; Lorenzoni, F C; Grigoletto, F (Plant Systematics and Evolution, 1983)
The exine architecture and some quantitative parameters (polar and equatorial axes and their ratio) of pollen grains allow a clear discrimination between groups of Mediterranean oak species. For the differentiation of species within groups only the quoted parameters prove useful.
Keywords: Angiosperms; Fagaceae; Pollen exine architecture; pollen grain size and form; Quercus